Cultural-psychological Alienation and its Effect in Teaching the Ability to Stand on the Head in the Gymnastics for Students in College of Physical Education and Sports Sciences - AWS Yousif Khelfa (Journal of Global Pharma Technology, 2016)
The basic ground-based movements in learning skills on all other devices, not without these skills difficulties. The problem of research is that there is a weakness in the orientation towards learning skills. The problem of research is summarized by the following question: Is psycho-cultural alienation the reason for the weak tendency towards learning skills or other reasons? What is the relationship between psycho-cultural alienation in the performance of this skill? To achieve the objectives of research will conclude the researcher to the actions achieved, including the identification of psychological alienation levels - cultural at the College of Physical Education and Sports Science students, and to know the relationship between psychological alienation - cultural and learn the skill of standing on the head. Is there a relationship of statistical significance between psychological and cultural alienation and the ability to stand on the head and the researcher used the descriptive method to suit the nature of the problem. The study sample was randomized to 30 students from the second stage of the Faculty of Physical Education and Sports Sciences, Thi-Qar University. It was found that there is a significant correlation between psychological and cultural alienation and learning the ability to stand on the head. So as not to attract second-stage students to practice skill. The teacher's failure to use the principle of reinforcement and correction of errors that may occur during performance leads to a poor approach to learning skills. The researcher recommended the use of a good method in the gymnastics to clarify and absorb the skill technique. And the need to use the principle of reinforcement. And the need to provide the appropriate educational environment.Keywords: Cultural-psychological alienation, gymnastics and Sports Sciences.